Drosophila CK2 regulates eye morphogenesis via phosphorylation of E(spl)M8. - Karandikar, U.C.; Trott, R.L.; Yin, J.; Bishop, C.P.; Bidwai, A.P. (Mechanisms of Development, 2004)
The Notch effector E(spl)M8 is phosphorylated at Ser159 by CK2, a highly conserved Ser/Thr protein kinase. We have used the Gal4-UAS system to assess the role of M8 phosphorylation during bristle and eye morphogenesis by employing a non-phosphorylatable variant (M8SA) or one predicted to mimic the 'constitutively' phosphorylated protein (M8SD). We find that phosphorylation of M8 does not appear to be critical during bristle morphogenesis. In contrast, only M8SD elicits a severe 'reduced eye' phenotype when it is expressed in the morphogenetic furrow of the eye disc. M8SD elicits neural hypoplasia in eye discs, elicits loss of phase-shifted Atonal-positive cells, i.e. the 'founding' R8 photoreceptors, and consequently leads to apoptosis. The ommatidial phenotype of M8SD is similar to that in Nspl/Y; E(spl)D/+ flies. E(spl)D, an allele of m8, encodes a truncated protein known as M8*, which, unlike wild type M8, displays exacerbated antagonism of Atonal via direct protein-protein interactions. In line with this, we find that the M8SD-Atonal interaction appears indistinguishable from that of M8*-Atonal, whereas interaction of M8 or M8SA appears marginal, at best. These results raise the possibility that phosphorylation of M8 (at Ser159) might be required for its ability to mediate 'lateral inhibition' within proneural clusters in the developing retina. This is the first identification of a dominant allele encoding a phosphorylation-site variant of an E(spl) protein. Our studies uncover a novel functional domain that is conserved amongst a subset of E(spl)/Hes repressors in Drosophila and mammals, and suggests a potential role for CK2 during retinal patterning.